TANGGUNGJAWAB PENGAWAS TERMINAL DALAM MENEGAKKAN KETERTIBAN DAN KEAMANAN ANGKUTAN UMUM - Sayudi, Moh Husen; Subekti, Subekti; Amiq, Bachrul (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study was motivated by the important role of terminal supervisors in maintaining order and safety in public transportation, which often faces various administrative, technical, operational, ethical, and legal violations. This study formulates two main issues: the duties and responsibilities of supervisors in enforcing order and safety. The method used is normative juridical with a legislative and conceptual approach. The results of the study show that violations include vehicles without route permits, unroadworthy vehicles, shadow terminals, and violations of service ethics and traffic laws. Meanwhile, the implementation of terminal supervisors' duties still faces various obstacles, such as limited human resources, limited authority, a lack of technological facilities, and a lack of synchronization of regulations between agencies. This study emphasizes the importance of strengthening legal authority, training, and inter-agency synergy to improve the effectiveness of supervision at terminals